Type C virus and immunoglobulin A production by murine myeloma MOPC-315: two independent activities. - Gazit, A (1979)
The suspected correlation between cessation of type C virus production and halt in immunoglobulin secretion by murine myeloma cells was studied. Employing two variants of the murine myeloma MOPC-315, immunoglobulin A-producing and nonproducing cells, we demonstrated that the two myelomas release similar levels of type C viruses which share common nucleotide sequences and that the viral genomes are equally expressed within the cells. Thus, the suggested relation between these two activities does not apply for MOPC-315 cells and probably for other murine myelomas also.